Proyecto de restauración e inserción de nuevo uso de la antigua estación de ferrocarril de Queréndaro - Zavala Loaiza, Ana Emma (Universidad Michoacana de San Nicolas de Hidalgo, 2013)
The present work of investigation and proposal of restoration and new use of the Old Railroad station of Queréndaro, has as purpose the safeguarding and valorization of the building that is in disuse since the privatization of the Mexican railroads was carried out, Leaving this type of industrial and railroad heritage in complete abandonment, resulting in the loss of large number of buildings of this typology so particular represented a way of life of the population. The investigation covered several stages for its realization, starting with the prospecting of the building, resulting in the registration and removal of materials and construction systems, deteriorations and alterations present in the property, data that were reflected in documents and corresponding planimetry. Subsequently developed the part corresponding to the investigation, which contemplated the historical, legal, environmental aspects, as well as the analysis of the theoretical positions on restoration and conservation of the heritage. Once the field and research activities were carried out, the criteria for intervention and restoration of the building were established, as well as the proposal for the new use of the building, thereby achieving safeguarding, value creation and a new useful life for the building.

El presente trabajo de investigación y propuesta de restauración y nuevo uso de la Antigua Estación de ferrocarril de Queréndaro, tiene como propósito la salvaguarda y puesta en valor del edificio que se encuentra en desuso desde que la privatización de los ferrocarriles mexicanos se llevó a cabo, dejando a este tipo de patrimonio industrial y ferrocarrilero en completo abandono, dando como resultado la pérdida de gran número de edificaciones de esta tipología tan particular representó una forma de vida de la población. La investigación abarcó varias etapas para su realización, iniciando con la prospección del edificio, dando por resultado el registro y levantamiento de los materiales y sistemas constructivos, los deterioros y alteraciones presentes en el inmueble, datos que se plasmaron en documentos y planimetría correspondiente. Posteriormente se desarrolló la parte correspondiente a la investigación, la cual contempló los aspectos históricos, legales, ambientales, así como el análisis de las posturas teóricas sobre restauración y conservación del patrimonio. Una vez realizadas las actividades de campo e investigación se establecieron los criterios de intervención y restauración del inmueble, así como la propuesta para el nuevo uso del edificio logrando con ello la salvaguarda, puesta en valor y una nueva vida útil para el inmueble
Facultad de Arquitectura. Especialidad en Restauración de Sitios y Monumentos
Keywords: info:eu-repo/classification/cti/4; FA-E-2013-0134; Patrimonio; Industrial; Ferrocarril; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3186